Avifauna in settlement zone of Kiev - Шупова, Т. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
In settlement zone of Kiev 114 species of birds of 17 orders have been observed. 86 species of birds (15 orders) are nesting. The density of nesting birds in weakly transformed biotopes is below the average for the region as a whole. In residential districts 20,3–43,0% of birds nest and weakly transformed biotopes are inhabited by 52,3–80,2% of the species of birds that nest in Kiev. Graphs of dominance-diversity of the birds indicate the absence of balanced development of avifauna in urban ecosystems of Kiev. Variety of species diversity of birds in residential areas is 2–3 times lower than in weakly transformed biotopes. In all biotopes synanthropic birds dominate. In the districts of multistory buildings and parks birds live in conditions of overcrowding population. Complex of nesting birds in parks occupy an intermediate position between complexes of birds of weakly transformed biotopes and of residential districts.